Pentingnya Sumber Daya Manusia yang Berkualitas dalam Rangka Pelayanan Publik pada Desa Wisata Teh Jamus Di Wilayah Perkebunan Teh Jamus, Kabupaten Ngawi, Jawa Timur - Budi Iriani Yudaningrum (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2021)
This Research has purposes to: 1) To analyze how the background of the establishment of tea plantations Jamus .2) To analyze how the development of tea plantations Jamus 1984-2001 . 3) To analyze how to impact tea plantation estates Jamus on surrounding communities. The method used in this study is a historical method. The initial phase of this research is heuristic phase, realized by interviews with relevant sources, including archival collection of the Central Bureau Statstik Archive, Archive of PT. Candi Loka. And literature. The data were then criticized by descriptive analysis, the analysis illustrates a pristiwa based on causal relations from a historical phenomenon in certain situations. Analysis of this data was obtained from documents, library research, and interviews, and then arranged in a historiography. The purpose of this activity is to combine the facts obtained in the research into the story of the history of resources is not a historical narrative. The results showed that the company of plantations in an area has an impact on the socioeconomic life of the people around the plantation. The development of the plantation resulted in a shift in the livelihood of the population from farmers to plantation workers. So it has a positive and negative impact on society. The Company has a responsibility to all stakeholders, including the communities around the plantation, the environment and the government in which the company is located.